Does membership on the UN security council influence IMF conditionality? - Dreher, Axel; Sturm, Jan-Egbert; Vreeland, James Raymond (Cege discussion paper, 2010)
We investigate whether elected members of the United Nations Security Council receive favorable treatment from the International Monetary Fund (IMF), analyzing panel data on the level of conditionality attached to (a maximum of) 314 IMF arrangements with 101 countries over the period of 1992 to 2008. We find a negative relationship: Security Council members receive about 30 percent fewer conditions attached to the loans that they receive from the IMF. We conclude that conditionality is softer for these countries because the major shareholders of the IMF desire influence over the Security Council. -- IMF ; UN Security Council ; Voting ; Aid ; Conditionality
Keywords: 1984-2004; Arbeitspapier; Graue Literatur